2008
DOI: 10.1371/journal.ppat.1000026
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Pili Are Composed of Protofilaments Exposing Adhesive Clusters of Rrg A

Abstract: Pili have been identified on the cell surface of Streptococcus pneumoniae, a major cause of morbidity and mortality worldwide. In contrast to Gram-negative bacteria, little is known about the structure of native pili in Gram-positive species and their role in pathogenicity. Triple immunoelectron microscopy of the elongated structure showed that purified pili contained RrgB as the major compound, followed by clustered RrgA and individual RrgC molecules on the pilus surface. The arrangement of gold particles dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(174 citation statements)
references
References 55 publications
9
162
2
Order By: Relevance
“…Our data using whole bacteria as well as purified pilus components further implicate a specific protein, RrgA, as the major determinant of TLR2 activity. RrgA has been described as an adhesin and binds to fibronectin, collagen 1, and laminin (17,50). Pilus-or RrgA-negative mutants of pneumococci have been shown to be relatively less virulent than their wild type isogenic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Our data using whole bacteria as well as purified pilus components further implicate a specific protein, RrgA, as the major determinant of TLR2 activity. RrgA has been described as an adhesin and binds to fibronectin, collagen 1, and laminin (17,50). Pilus-or RrgA-negative mutants of pneumococci have been shown to be relatively less virulent than their wild type isogenic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Pilus formation requires the expression of seven genes encoded by the rlrA pathogenicity islet, including a RofA-like transcriptional regulator (RlrA), three sortases (SrtC-1, SrtC-2, and SrtC-3), and three structural proteins (RrgA, RrgB, and RrgC) (10). Electron microscopy observations of immunogold-labeled pneumococcus allowed investigations on the structural composition of the pilus and showed that RrgB is the major pilin subunit forming the elongated fiber shaft, but data concerning the precise localization of the minor RrgA and RrgC pilin subunits remained controversial (10,(25)(26)(27). Recently, an elegant structural analysis of the native pneumococcal pilus using a combination of electron microscopy techniques provided evidence that the RrgB-shaft is composed of monomeric covalently linked subunits oriented headto-tail (28).…”
mentioning
confidence: 99%
“…Another minor pilin subunit, RrgA of Streptococcus pneumonia, promotes bacterial adherence to respiratory epithelia (31). RrgA has been reported to bind to the extracellular matrix components fibronectin, collagen I, and laminin (32). Finally, Group A streptococcal pili engage the scavenger receptor gp340 on pharyngeal cells to promote adherence and aggregation (33).…”
Section: Discussionmentioning
confidence: 99%